2016
DOI: 10.1177/1468797616682615
|View full text |Cite
|
Sign up to set email alerts
|

Selling cruises: Gender and mobility in promotional brochures

Abstract: Leisure cruising combines movement and stativity in a particular tourist experience: users are supposed to enjoy very different activities, with the movement of the ship guiding them to their destinations. This paper analyses visual representations of gender and mobility in over 600 images collected from leisure cruise promotional brochures by taking advantage of a qualitative methodology and by focusing on narratives related to themes of pleasure, work, age, and contact with nature/culture. The results stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Similarly, Gutberlet (2016a and 2016b) analysed sociocultural impacts of mega-cruise tourism in a market opposite the port in Muscat. Vanolo and Cattan (2017) investigated visual representations of cruise experiences in promotional brochures, focusing on gender and mobility. Most articles focus on the economic, social and environmental impacts of cruise tourism (Cusano et al, 2017; Gutberlet, 2016b; Hritz and Cecil, 2008; Larsen et al, 2013; Larsen and Wolff, 2016; Lűck et al, 2010; MacNeill and Wozniak, 2018) the globalization and its effects on the production and consumption on board (Da Cruz, 2018; Wood, 2000) as well as on the work environment on board (Gibson, 2008; Weaver, 2005a).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Gutberlet (2016a and 2016b) analysed sociocultural impacts of mega-cruise tourism in a market opposite the port in Muscat. Vanolo and Cattan (2017) investigated visual representations of cruise experiences in promotional brochures, focusing on gender and mobility. Most articles focus on the economic, social and environmental impacts of cruise tourism (Cusano et al, 2017; Gutberlet, 2016b; Hritz and Cecil, 2008; Larsen et al, 2013; Larsen and Wolff, 2016; Lűck et al, 2010; MacNeill and Wozniak, 2018) the globalization and its effects on the production and consumption on board (Da Cruz, 2018; Wood, 2000) as well as on the work environment on board (Gibson, 2008; Weaver, 2005a).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that gender and age significantly affect the perceived image of tourism destinations (Baloglu, 1997;Baloglu & McCleary, 1999;Chen & Kerstetter, 1999;Walmsley & Jenkins, 1993). Over the years, relationships between gender, culture and space in the sense of tourism have been emerging as research topics in tourist studies (Aitchison, 1999(Aitchison, , 2001Anderson, 1996;Pritchard & Morgan, 2000, 2005; as cited in Vanolo & Cattan, 2016). Vanolo and Cattan (2016) in their article analyzing representations of gender and mobility in cruise promotional brochures, outline how activities in tourism are gender-influenced.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Disney cruises). These big ships oftentimes have seductive names such as Caribbean Princess, Harmony of the Seas, or Norwegian Spirit Vanolo and Cattan (2017). have studied the narratives about gender and mobility in promotional brochures for cruises, pointing out their use of discourses of pleasure and intimacy, of 'happy ageing', professionality of the workforce and exoticism of both urban and natural destinations.…”
mentioning
confidence: 99%